Analysis of hybrid ARQ in 3GPP LTE systems - Sandrasegaran, Kumbesan; Reeves, Scott; Mohd. Ramli, Huda Adibah; Basukala, Riyaj (IEEE., 2010)
The use of Hybrid ARQ in wireless networks is to provide fast re-transmits and to lower the overall error rate. The performance of HARQ schemes is a well studied field, with many results to draw from in the literature. An area that is less researched is what impact Hybrid ARQ has on LTE systems. We are, specifically, interested in looking at the system delay, but also at how HARQ behaves when used with a packet scheduler. A further area of interest is when HARQ is a drawback on the system throughput. This paper aims to look at all three of these areas.